PEMAHAMAN GURU BK TENTANG PENDEKATAN KONSELING YANG DIGUNAKAN DALAM PELAKSANAAN KONSELING PERORANGAN DI SMP NEGERI KECAMATAN SANGIR JUJUAN KABUPATEN SOLOK SELATAN - Dewi, Yetrina; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
This research based on phenomenon that occurred in the field counselor do not understand the counseling approach. This research see how the counselor understanding about counseling approach thatÂ  used in implementation of individual counseling at Junior High School District Sangir Jujuan Kabupatan Solok Selatan, the extent of the problem, was: 1) counselors understandingÂ  aboutÂ  directive counseling approach that used in implementation of individual counseling,2) counselorsâunderstandingÂ  about Â non-directive counseling approach that used in implementation of individual counseling, 3)counselorsâ understanding about eclecticcounseling approach that used in implementation of individual counseling.Type of this research was qualitative research. This study takes the counselor in Junior High School District Sangir Jujuan Kabupaten Solok Selatan as research informants. Date were collected through interviews and documentation. The results describe that counselors understanding about counseling approaches that used in implementation of individual counseling not understand the existing approach to counseling,it was visibly from counselorsâ understanding in basic concepts and the process of counseling, do not give full freedom the learners in expressing the problem, the counselor was more emphasizes guided by a theory because teachers do not pay attention to development of counseling and guidance various forms of service.